Analysis of the Impact of Radiation and Albedo on Variations in Earth's Surface Temperature - Nurfaizah, Dwi Ayu; Dahliani, Eka; Widyaputri, Mutya Ardha (Universitas PGRI Palembang, 2025)
Solar radiation reaching the Earth is partially absorbed by the surface and partially reflected back into the atmosphere as shortwave and longwave radiation. This study aims to analyze the impact of radiation and albedo on variations in Earth’s surface temperature. The experimental procedure involved exposing different surface types—soil, water, and rock—to light for 20 minutes and then observing their behavior without light for another 20 minutes. The results indicate that low-albedo surfaces absorb more radiation, leading to a temperature increase of 3°C, from 26°C to 29°C. Medium-albedo surfaces, such as rock, experienced a similar temperature rise of 3°C (from 28°C to 31°C), whereas high-albedo surfaces, such as water, showed only a 1°C increase (from 27°C to 28°C). These findings highlight the significant role of albedo in regulating surface temperature fluctuations. Surfaces in high-albedo areas tend to cool more rapidly than those in low-albedo regions. This demonstrates that albedo directly influences radiation absorption and temperature change, making it an effective instructional example for understanding physical concepts such as heat transfer and energy balance at the Earth’s surface.